The effects of aerobic and anaerobic training programs applied to elite wrestlers on Body Mass Index (BMI) and blood lipids - Demirel, N.; Özbay, S.; Kaya, F. (Journal of Education and Training Studies, 2018)
The purpose of this study is to analyse the effects of aerobic and anaerobic training programs applied to elite wrestlers on body mass index (BMI) and blood lipids. 20 elite wrestlers, whose average age is (experimental group; 15.20±4.61, n=10), control group; 15.90±2.08, n=10), participated in the study and they were randomly divided into two groups. Strength and endurance training programme based on "one day aerobic, one day anaerobic" principles was applied to the experimental group six days a week for eight weeks. The control group went on doing normal routine wrestling technical training. Before and after eight-week training program, BMI, Triglyceride, HDL-C, VLDL, Cholesterol, LDL blood values were taken from the experimental and the control group by body analyser. According to the results of the study, none of the blood lipid indicators of the control group did significantly changed from pretest to posttest. (p>0.05). However, HDL-C, cholesterol and LDL values from blood lipids indicators of the experimental group changed significantly from pretest to posttest. (p<0.05). There were no significant changes in body mass index (BMI), Triglyceride and VLDL. As a result, this study revealed that there was no significant difference in the control group which did exercise routinely, while the training programme with changeable type and volume made significant differences in the experimental group.In statistical analyses, paired- samples t test was used for intra-group comparisons, and independent sample t test was used for inter-group comparisons. The significance level was determined as p<0.05. For all the values, mean and standard deviation were used.